Cover Picture: Similarity of functional connectivity patterns in patients with multiple sclerosis who void spontaneously versus patients with voiding dysfunction (Neurourology and Urodynamics 38/2019). Issue 1 (28th December 2018) - Khavari, Rose; Elias, Saba N.; Boone, Timothy; Karmonik, Christof
Abstract : Cover : The cover image, by Rose Khavari et al., is based on the Original Article Similarity of functional connectivity patterns in patients with multiple sclerosis who void spontaneously versus patients with voiding dysfunction DOI:10.1002/nau.23837 .